Towards an Extensible and Secure Cloud Architecture Model for Sensor Information System - Pengfei You; Zhen Huang (International Journal of Distributed Sensor Networks)
Sensor information system is a specific distributed information management system for applying sensor data and aims to effectively process, manage, and analyze data emanating from sensor networks. Recently, with the development of sensor networks, sensor information system encounters many challenges, such as huge and diverse data, heterogeneous clients, scalability, and security. In this paper, we propose an extensible and secure cloud architecture model for sensor information system. Firstly, we describe the composition and mechanism of the architecture model using cloud paradigm. Secondly, we design the security solution for accessing sensor data and information services inside the architecture. This security solution ensures legal access and use for sensor data and information services and avoids illegal breach for user data in the cloud environment. In particular, a certificate authority (CA) based Kerberos protocol is proposed to provide strong identity authentication. At last, we introduce the experiment deployment for the architecture. This architecture fully utilizes the virtualization technology and cloud service functions and builds an extensible cloud platform environment supplying scalable, flexible, reliable, and secure sensor information services, which aims to solve the challenges encountered by the present sensor information system. The simulation experiment results show that the architecture gets high performance and stability throughout, while keeping scalability and flexibility brought by cloud.